Physicochemical Properties of Phosphate Pregelatinized Musa balbisiana Starch as Pharmaceutical Excipient - Deni Anggraini; Anita Lukman; Hilwan Y. Teruna (Universitas Padjadjaran, Indonesia)
Starch is among the important pharmaceutical excipient, which is particularly used as filler in the tablet formulation and suspending agent. Starch from natural source has a potential to be developed as pharmaceutical excipient with comparable characteristics, including starch from Musa balbisiana (M. balbisiana). This study aimed to synthesize and evaluate physicochemical properties of phosphate pregelatinized M. balbisiana starch. We isolated the starch from M. balbisiana and performed pregelatinization. Since pregelatinized starch still could experience retrogradation which cause syneresis, chemical modification of pre-gelatinized starch was conducted using 5% of sodium tripolyphosphate at pH of 9-10. Physicochemical properties of phosphate pregelatinized starch were then investigated. It included the assessment of its organoleptic, pH, water content, particle size distribution, angle of repose, swelling power, amylose content, adsorbs isotherm, and particle analysis using Scanning Electron Microscope (SEM). Phosphate-pregelatinized M. balbisiana starch had low swelling power, better flow properties and viscosity. It can be used particularly in the formulation of slow released tablets and suspending agents in suspension formula.Keywords: pregelatinized starch, Musa balbisiana, psychochemical properties, excipients